Learners’ Perceptions on WhatsApp Integration as a Learning Tool to Develop EFL Spoken Vocabulary - Khan, Raja Muhammad Ishtiaq; Radzuan, Noor; Farooqi, Shahzad; Shahbaz, Muhammad; Khan, Mohammad (Universitas Negeri Makassar, 2021)
Technology integration has a great impact on learners’ learning styles and everyday life, where various encouraging responses come across in language learning institutions through the use of mobile technology. WhatsApp application instantly transfers information in different modes. At the present time it can be effectively used as a platform to engage learners with conventional classroom setting. The present study is an attempt to investigate learners’ attitudes towards WhatsApp application and their intention for future use. 32 EFL learners were exposed to learn vocabulary by the use of WhatsApp application for a period of 6 weeks. Data were collected by using questionnaire and semi-structured interviews. The result exhibited higher levels (M= 4.4 and Mode 4.37) of the mean scores of the learners’ perception and (M= 4.3) on WhatsApp Usage attitudes. The finding of the study indicated that learners expressed positive attitudes in using WhatsApp applications for vocabulary development. The present study also suggests that the integration of WhatsApp should be fortified to learners, instructors and institutions in developing other language learning process.